PENGARUH GAYA HIDUP TERHADAP PERILAKU PEMBELIAN KONSUMEN KOSMETIK AVON DI SURAKARTA - Paningrum, Destina (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2012)
Background: Cosmetic is one of needs that is always used by thewomen. Now, it will beÂ  anÂ  importantÂ  thingÂ  firÂ  everyÂ  woman,Â  oneÂ  ofÂ  theÂ  mostÂ  famousÂ  cosmeticÂ  isÂ  Avon.Â  Avon must be able to satisfied the consumerâs needs, andone of them is the influence of lifestyle that growth in each dimension, such as the activity, opinion, and interest. The Research Purpose: This research is aimed to know how a lifestyle thatgrows in the activity, opinion, and interest dimension and what kinds of dimension that is influential to the Avonâs consumers ResearchÂ  Method:Â  TypeÂ  ofÂ  thisÂ  researchÂ  isÂ  surveyÂ  research,Â  whereÂ  the sample derivationÂ  isÂ  doneÂ  purposivelyÂ  withÂ  ClassifiedÂ  SimpleÂ  RandomÂ  SamplingÂ  MethodÂ  around SurakartaÂ  areas,Â  usingÂ  5Â  counters,Â  byÂ  100Â  respondentsÂ  andÂ  thenÂ  itÂ  isÂ  analizedÂ  byÂ  double regression, discriminant, F test, and t test. ResearchÂ  finding: (1)Â  ActivityÂ  ofÂ  dimensionÂ  lifestyleÂ  isÂ  influential positivelyÂ  and significantlyÂ  onÂ  cosmeticÂ  buying-seenÂ  fromÂ  sellingÂ  intensity.Â  (2)Â  ActivityÂ  andÂ  opinionÂ  of dimension lifestyles are influential positively andsignificantly on cosmetic buying-seen from theÂ  numberÂ  ofÂ  product.Â  (3)Â  ActivityÂ  andÂ  interestÂ  of dimensionÂ  lifestylesÂ  areÂ  influential positively and significantly on cosmetic buying-seen from the kinds of product. (4) Activity of dimension lifestyles is the most influential lifestyle dimension-seen from selling intensity, number of product, and the kinds of product.